Evolution of technology for commercial vehicle safety - Peter Sweatman (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2017)
Heavy commercial vehicle technology for safety has developed in capability and application and is having a positive impact on truck safety. And the potential for further safety improvements is exciting. We wish to place the evolution of such technology in perspective with related developments for light vehicles and the rapid convergence of a number of transformational technologies in transportation. These technologies affect vehicles, drivers and infrastructure, and are now having a much broader impact on adjacent industries and new "disruptive" entrants in the transportation sector. Transformational technologies under consideration include connected vehicles (CVs) and automated vehicles (AVs), as well as shared mobility (SM), smart cities and communities (SCCs), alternative-fuel vehicles (AFVs) and big data analytics. As heavy vehicle technologies move beyond Advanced Collision Avoidance Systems (ACAS) towards connected and automated vehicles (CAV), it is important to consider contextual issues that apply to freight vehicles very differently from light vehicles. It is hoped that the roundtable will shed light on the way forward for the heavy vehicle sector in its own technological right. CV is more significant for heavy commercial vehicles than for light vehicles because the organized nature of heavy vehicle operations benefits more from connectivity. Fleets have an important role to play in deploying the technology, engaging with smart cities and communities, establishing connected corridors and precincts, and developing new accommodations for heavy vehicles, including signal priority and truck parking. AV for heavy commercial vehicles offers immediate benefits in terms of automated features that assist drivers. Automated features that support or relieve the heavy vehicle driver in well-defined circumstances will play an important role in advancement of the freight industry. Some significant uncertainties need to be navigated before highly-automated vehicles (HAVs) play an important role for heavy vehicles.
Keywords: 330; Lastkraftwagen; Verkehrssicherheit; Sicherheitstechnik; Innovationsdiffusion; Transportmanagement